The Theories of Federal Habeas Corpus - Evan Tsen Lee (Washington University Law Quarterly, 1994)
This Article makes two principal arguments. First, the best interpretation of the federal habeas corpus statute would not embrace any theory to the exclusion of all others. To some degree, the Court has had trouble settling on a theory of habeas because the theories under consideration are oversimple. What makes the most sense is a hybrid approach to habeas jurisdiction. This hybrid theory would hold that federal habeas relief is justified whenever: (1) state courts have failed to accord the petitioner's constitutional claims a full and fair hearing; (2) the petitioner has made a colorable showing of innocence and that a constitutional violation may have caused the conviction; or (3) when the likelihood of deterring future constitutional violations outweighs the costs of relief. Federal habeas relief would be impermissible in the absence of one of these three circumstances. Adoption of this hybrid theory would move the Court toward stability in its habeas jurisprudence. Second, the Article focuses on how the third prong of the hybrid theory-the deterrence concept-would work in practice. Although there is room for disagreement about precisely how much deterrence would result from particular grants of habeas relief and about the costs of such relief, I believe that the deterrence theory would eventually become a powerful force in favor of relatively broad federal habeas review.
Keywords: Habeas corpus; Judges; United States. Supreme Court; United States